Potential Health Effects of Heavy Metals and Carcinogenic Health Risk Estimation of Pb and Cd Contaminated Eggs from a Closed Gold Mine Area in Northern Thailand - Paweena Aendo; Michel De Garine-Wichatitsky; Rachaneekorn Mingkhwan; Kamonthip Senachai; Pitchaya Santativongchai; Praphaphan Krajanglikit; Phitsanu Tulayakul (Foods, 2022)
Gold-mining activities have been demonstrated to result in significant environmental pollution by Hg, Pb, and Mn, causing serious concerns regarding the potential threat to the public health of neighboring populations around the world. The present study focused on heavy-metal contamination in the eggs, blood, feed, soil, and drinking water on chicken farms, duck farms, and free-grazing duck farms located in areas < 25 km and > 25 km away from a gold mine in northern Thailand. In an area < 25 km away, Hg, Pb, and Mn concentrations in the eggs of free-grazing ducks were significantly higher than > 25 km away (p < 0.05). In blood, Hg concentration in free-grazing ducks was also significantly higher than those in an area > 25 km away (p < 0.05). Furthermore, the Pb concentration in the blood of farm ducks was significantly higher than in an area > 25 km away (p < 0.05). The concentration of Cd in drinking water on chicken farms was significantly higher for farms located within 25 km of the gold mine (p < 0.05). Furthermore, a high correlation was shown between the Pb (r2 = 0.84) and Cd (r2 = 0.42) found between drinking water and blood in free-grazing ducks in the area < 25 km away. Therefore, health risk from heavy-metal contamination was inevitably avoided in free-grazing activity near the gold mine. The incremental lifetime cancer risk (ILCR) in the population of both Pb and Cd exceeded the cancer limit (10−4) for all age groups in both areas, which was particularly high in the area < 25 km for chicken-egg consumption, especially among people aged 13–18 and 18–35 years old. Based on these findings, long-term surveillance regarding human and animal health risk must be strictly operated through food chains and an appropriate control plan for poultry businesses roaming around the gold mine.